Vie perdue de Guillaume Longue-Épée († 942) état des recherches en cours - Jacques Le Maho (Tabularia)
The comparative analysis of several texts dating back from the 10th and 11th centuries, among which the Planctus on the death of Guillaume the long sword, the volumes II and III of the work by Dudon of St Quentin, the History of France by Richer of Reims and the Gesta of Jumièges, brings to the establishment that all these texts, in various degrees, probably derive from one narrative source – lost now –: A life of Guillaume the long sword, second earl of Normandy (927-942). Most certainly written in the monastery of St Mesmin of Micy (Loiret), some time between 950 and 963, this work is to be ascribed to Annon, abbot of Micy and Jumièges (died in 970/973), a man who, for some years, has also been identified as the author of the lives of saint Aycadre and saint Hugues of Jumièges as well as of the life of saint Eucher of Orleans. The research which is being currently carried out notably deals with an attempt at rebuilding the synopsis of the Vita and with the origins of the volumes II and III by Dudon, these books being acknowledged now as a simple rewriting of the Vita Guillelmi by Annon, and no longer as the founding text of the historiography of the first two earls.